Determinants of Employee Performance: Organizational Support, Organizational Commitment and Transformational Leadership (Literature Review) - Wayan Gede Endra Bratha; Hapzi Ali (Dinasti Publisher, 2024)
The impact of organizational support, organizational commitment and transformational leadership on employee performance is an academic review of literature in the area of human resource management science. The aim of this article is to develop hypotheses about the connections between different variables, which will be utilized in upcoming research. Research materials derive from digital repositories, academic search engines, and scholarly databases. The writing method involves library research using articles, journals, and e-books. The analysis is qualitative and descriptive. The findings of this paper: 1) Organizational Support affects Employee Performance; 2) Organizational Commitment affects Employee Performance; and 3) Transformational Leadership affects Employee Performance.